A9.12 Effects of endothelin-1 and its receptor antagonism on the endothelial-to-mesenchymal transition in cultured human dermal microvascular endothelial cells. (31st January 2014) - Soldano, S; Brizzolara, R; Paolino, S; Seriolo, B; Montagna, P; Sulli, A; Cimmino, M A; Ruaro, B; Cutolo, M
Abstract : Background and Objectives: The early events involved in the pathogenesis of many connective tissue diseases, such as systemic sclerosis (SSc) include endothelial/microvascular damage and activation of myofibroblasts responsible for excessive deposition of extracellular matrix components (i.e. collagens) (1-4). Recent studies showed that myofibroblasts may originate from the endothelial-to-mesenchymal transition (EndoMT) process (5). To investigate the possible effects of endothelin-1 (ET-1) and its receptor antagonist (ETA/B RA) on the EndoMT in cultured human dermal microvascular endothelial cells (HMVECs). Materials and Methods: HMVECs (Lonza Clonetic, Switzerland) were treated with or without ET-1 (100 nM, EnzoLife Science, UK) for 6 days, in accordance with recent studies (6, 7). Cells were also pre-treated (1 hr) with ETA/B RA (bosentan, 10µM) before being treated with ET-1. The expression levels of fibroblast specific protein-1 (S100A4, S100 calcium binding protein A4) and α-smooth muscle actin (α-SMA), both markers of the myofibroblast phenotype, and vascular endothelial growth factor receptor (VEGFR) as well as platelet endothelial cell adhesion molecule (PECAM-1 or CD31), markers of the endothelial phenotype, were investigated by quantitative real time-polimerase chain reaction (qRT-PCR). S100A4 expression was also evaluated by immunocytochemistry using primary antibody to human S100A4 (dilution 1:100, Santa Cruz Biotechnology, Dallas) whereas α-SMA and CD31 expressions were investigated by immunofluorescence using primary antibodies to human α-SMA (dilution 1:50, Dako Cytomation, Denmark) and CD31 (dilution 1:200, CellSignaling Technology, Denver, USA). Data were obtained from 5 different experiments. Statistical analysis was performed using the Mann-Whitney non-parametric t-test and the p-values lower that 0.05 were considered statistically significant. Results: ET-1 induced a statistically significant increase in S100A4 and α-SMA expressions (p = 0.01 vs. untreated cells). Interestingly, ET-1 was able to reduce the VEGFR expression in a statistically significant manner (p = 0.03 vs. untreated cells) without modulating CD31 expression. ETA/B RA contrasted the ET-1-mediated increase in S100A4 expression and, less efficiently, the increase in α-SMA expression. Moreover, ETA/B RA was able to partially contrast the decrease in VEGFR expression induced by ET-1. All these data were obtained by qRT-PCR and confirmed by immunocytochemistry for S100A4 and by immunofluorescence for α-SMA and CD31. Conclusions: Results indicate that ET-1 seem to activate the EndoMT, by inducing the expression of markers of mesenchymal/myofibroblast phenotype (S100A4 and α-SMA), and at the same time, by reducing the expression of endothelial phenotype marker (VEGFR) in cultured human dermal microvascular endothelial cells (8). ETA/B RA might contrast the ET-1-mediated induction of EndoMT. References: Wynn TA et al. Nat Med 2012;18:1028-40. Chaudury V et al. J Cutan Pathol 2007;34:147-53. Jimenez SA. ISRN Rheumatol 2013 Sep 23;2013:835948. Cutolo M et al. Nature Rev Rheumat 2010;6:578–87. Zeisberg EM et al. Nat Med 2007;13:952-61. Kitao A et al. Am J Pathol 2009;175:616-26. Wydyantoro B et al. Circulation 2010;121:2407-18. Soldano S et al. Arthrit & Rheum 2012;64(Supplement).